Catch quality and size selectivity in the Barents Sea bottom trawl fishery: effect of codend design and trawling practice - Brinkhof, Jesse Vallevik (Fisheries Research, 2019)
This study focused on two important issues on the Barents Sea bottom trawl fishery for Northeast Arctic cod (Gadus morhua L.); catch quality (i.e., the quality of the fish caught) and size selectivity. The high abundance of cod encountered in recent years in the Barents Sea, leading to subsequent large annual quotas, has led to increased interest in improving the quality of fish caught by trawls. This increasing interest in improving the quality of fish caught by trawls has also been driven by the increasing demands from the industry, retailers, and consumers for traceable high-quality products, as well as fish welfare. Although catch efficiency and size selectivity have been the major aspects of the bottom trawl fishery for decades, the focus on catch quality and how the quality of the catch is affected by the fishing process has remained limited. To ensure a sustainable fishery, in terms of ecological, societal, and economical sustainability, both catch quality and size selectivity are the two important factors that must be considered. In many cases, these two factors are interlinked, as a given change in a trawling procedure or trawl gear component with the aim of improving catch quality might simultaneously influence size selectivity. Therefore, in this thesis, I investigate the effect of a trawling practice (Paper I and II) and trawl codend design (Paper III and IV) on catch quality (Paper I and III) and size selectivity (Paper II and IV). The first part of my thesis (Paper I and II) presents a trawling practice, called buffer towing. It is claimed that this practice has a negative effect on both catch quality and size selectivity. Trawlers commonly re-deploy (“shoot”) the trawl directly after hauling a catch onboard. However, the approximate desired amount of fish is often caught before the catch from the previous haul has been processed. This issue frequently results in buffer towing, which entails lifting the trawl from the seabed and towing the catch midwater at low velocity until the onboard processing ...